The effect of various modes of occupational stress, job satisfaction, intention to leave and Absentism Companies Commission of Malaysia - Yahaya, Azizi; Yahaya, Noordin; Amat, Farhana; Bon, Abdul Talib; Zakariya, Zurihanmi (INSInet Publication, 2010)
This article highlights some of the major research findings regarding the causes of occupational stress within the organization and the implication on job satisfaction and intention to leave and absenteeism. The researcher chooses 100 employees in Companies Commission of Malaysia, a statutory body which regulated company and businesses. Pearson Product Moment Correlation to find out correlations and Multiple Linear Regression Technique were used to find out effect between variables. The finding indicates that factor such as external environment contribute to the occupational stress. This external factor is beyond the control of the organization. The occupational stress do not have direct effect on intention to leave and absenteeism but have direct negative effect on job satisfaction. Job satisfaction have negative effect on intention to leave and absenteeism.